Longitudinal care continuity and avoidable hospitalization: the application of claims-based measures - Shou-Hsia Cheng; Chi-Chen Chen; Yueh-Yun Lin (BMC, 2023)
Abstract Background Longitudinal continuity between a patient and his/her primary care physician is an important aspect in measuring continuity of care (COC). The majority of previous studies employed questionnaire surveys to patients to measure the continual relationship between patients and their physicians. This study aimed to construct a provider duration continuity index (PDCI) by using longitudinal claims data and to examine its agreement with commonly used COC measures. Then, this study investigated the effects of the various types of COC measure on the likelihood of avoidable hospitalization while considering the level of comorbidity. Methods This study constructed a 4-year panel (from 2014 to 2017) of the nationwide health insurance claims data in Taiwan. In total, 328,044 randomly selected patients with 3 or more physician visits per year were analyzed. Two PDCIs were constructed to measure the duration of interaction between a patient and his/her physicians over time. The agreement between the PDCIs and three commonly used COC indicators, the Usual Provider of Care index, the Continuity of Care Index, and the Sequential Continuity Index, were examined. Generalized estimating equations were conducted to examine the association between COC and avoidable hospitalization by the level of comorbidity. Results The results showed that the correlations among the three commonly used COC indicators were high (γ = 0.787 ~ 0.958) and the correlation between the two longitudinal continuity measures was moderate (γ = 0.577 ~ 0.579), but the correlations between the commonly used COC indicators and the two PDCIs were low (γ = 0.001 ~ 0.257). All COC measures, both the PDCIs and the three commonly used COC indicators, showed independent protective effects on the likelihood of avoidable hospitalization in three comorbidity groups. Conclusion The duration of interaction between patients and physicians is an independent domain in measuring COC and has a significant effect on health care outcomes.